DESIGN AND EVALUATION OF EARTHQUAKE RESISTANT BUILDING DIGITAL LIFESTYLE CENTER, BSD CITY WITH DUAL STRUCTURE SYSTEM - GUNAWAN (NIM: 15014089), MARVIN
These days, the seemingly unending advancement of technology provides a massive population capacity. With this increase and a stagnant space on the planet, emerge the needs of residency. One way to tackle this need, is the constructions of elevated buildings. This kind of construction, as does any kind of constructions, does not come free of problems. Beside the requirement of a more advanced understanding regarding the complexity in which an elevated building behaves, there is a growing concern about natural threats namely earthquakes. This particular final project is composed with the purpose of giving a sense of expertise and experience about regarding the design of an elevated building with dual structure system. The dual structure system mentioned are special moment frame and special reinforced concrete shear wall. This final project also shows a string of steps on designing an earthquake resistant elevated building. Said steps consist of the checking of earthquake design criteria, the checking of maximum allowable story drifts, the checking of P-Delta effect, the checking of fundamental periods, the checking of structural modal, the checking of minimum frame moment of 25% design lateral force capability, and the checking of redundancy factor. After all these steps, structural element design such as beam, column, joint, slab, and shear wall can can be performed. This design will be done with the aid of several softwares which later will be manually checked to provide insurance and further ensure the credibility the softwares computations.